Bold smugglers and DIY heroes - Cvar, Nina (Družboslovne razprave, 2025)
The article explores how gaming cultures in socialist Yugoslavia – particularly in Slovenia –are remembered and commemorated today. Drawing on the technostalgic momentum that has seen renewed interest in peripheral gaming histories, we examine how Yugoslavia’s unique geopolitical position and socialist experiment in self-management fostered vibrant do-it-yourself (DIY) computing and gaming cultures. Focusing on key memory sites – primarily the book Prva Bitnost and the documentary Tehnika ljudstvu – we: 1) outline the contexts of the emergence of Yugoslav games in the 1980s; 2) analyse how they are being narrativised through nostalgic lenses in the present; and 3) critique the exclusions embedded in these narratives. It is argued that these commemorative practices often reinforce mnemonic hegemony privileging male-coded heroism and entrepreneurial myth-making, while marginalising women, queer voices, and class-based experiences.
Keywords: colletive memory; DIY computing; do-it-yourself; do-it-yourself computing; gender and gaming; jugoslovanske videoigre; Kolektivni spomin; naredi-si-sam; naredi-si-sam računalništvo; spol in igre; technostalgia; tehnonostalgija; video games; Videoigre; Yugoslav video games